SOLAR AND MONTH ECLIPSE APPLICATIONS FOR SCHOOL STUDENT LEARNING BASIC USING MACROMEDIA FLASH MX - Mochamad Said Ade Santoso; Ristyawati, Skom, MMSI Ristyawati, Skom, MMSI (Jurnal Sistem Informasi, 2005)
Application Program eclipse of the Sun and the Moon for Elementary School Students Learning is a multimedia application program that contains some material about the eclipse of learning for children of primary school students in accordance with a guidebook currently available, packaged in an attractive form of assistance is also accompanied sound.These scientific writing illustrates how an application program making solar and lunar eclipses for elementary school students using Macromedia Flash MX and working under the operating systems Windows 98, Windows ME, XP. It is expected that applications can be useful to encourage elementary school students in studying the eclipse or also useful for children who are just starting to learn.